Australian recommendations for the management of hepatocellular carcinoma: a consensus statement. Issue 10 (13th December 2020) - Lubel, John S; Roberts, Stuart K; Strasser, Simone I; Thompson, Alexander J; Philip, Jennifer; Goodwin, Mark; Clarke, Stephen; Crawford, Darrell HG; Levy, Miriam T; Shackel, Nick
Abstract: Introduction: Hepatocellular carcinoma (HCC) is a leading cause of cancer deaths both globally and in Australia. Surveillance for HCC in at‐risk populations allows diagnosis at an early stage, when potentially curable. However, most Australians diagnosed with HCC die of the cancer or of liver disease. In the changing landscape of HCC management, unique challenges may lead to clinical practice variation. As a result, there is a need to identify best practice management of HCC in an Australian context. This consensus statement has been developed for health professionals involved in the care of adult patients with HCC in Australia. It is applicable to specialists, general medical practitioners, nurses, health coordinators and hospital administrators. Methods and recommendations: This statement has been developed by specialists in hepatology, radiology, surgery, oncology, palliative care, and primary care, including medical practitioners and nurses. The statement addresses four main areas relevant to HCC management: epidemiology and incidence, diagnosis, treatment, and patient management. A modified Delphi process was used to reach consensus on 31 recommendations. Principal recommendations include the adoption of surveillance strategies, use of multidisciplinary meetings, diagnosis, treatment options and patient management. Changes in management as a result of this statement: This consensus statement will simplify HCC patient management and reduce clinical variation. Ultimately, this should result in better outcomes for patients with HCC.